OBTAINING PRINTING INK FOR PRINTING MIXED FIBERS - Eshdavlatova Gulrukh Eshmamatovna (Web of Journals Publishing, 2023)
Thickening polymer compositions based on oxidized starch have been created. Thickening compositions of a new composition have been developed for printing mixed fabrics based on mixed fibers. The influence of the components of thickening compositions on the rheological properties of the composition depending on their concentration was studied. The development of a new composition of the thickening composition and its physicochemical properties have been established.
Keywords: printing ink, dye, composition, fabric printing, mixed fabrics, polyacrylamide, oxidized starch, color fastness.